Belimumab use during pregnancy: a summary of birth defects and pregnancy loss from belimumab clinical trials, a pregnancy registry and postmarketing reports. Issue 2 (5th October 2022) - Petri, Michelle; Landy, Helain; Clowse, Megan E B; Gemzoe, Kim; Khamashta, Munther; Kurtinecz, Milena; Levy, Roger A; Liu, Andrew; Marino, Rebecca; Meizlik, Paige; Pimenta, Jeanne M; Sumner, Kelsey; et al.
Abstract : Objective: Describe available data on birth defects and pregnancy loss in women with systemic lupus erythematosus (SLE) exposed to belimumab. Methods: Data collected from belimumab clinical trials, the Belimumab Pregnancy Registry (BPR), and postmarketing/spontaneous reports up to 8 March 2020 were described. Belimumab exposure timing, concomitant medications and potential confounding factors were summarised descriptively. Results: Among 319 pregnancies with known outcomes (excluding elective terminations), 223 ended in live births from which birth defects were identified in 4/72 (5.6%) in belimumab-exposed pregnancies and 0/9 placebo-exposed pregnancies across 18 clinical trials, 10/46 (21.7%) belimumab-exposed pregnancies in the BPR prospective cohort (enrolled prior to pregnancy outcome) and 0/4 belimumab-exposed pregnancies in the BPR retrospective cohort (enrolled after pregnancy outcome), and 1/92 (1.1%) in belimumab-exposed pregnancies from postmarketing/spontaneous reports. There was no consistent pattern of birth defects across datasets. Out of pregnancies with known outcomes (excluding elective terminations), pregnancy loss occurred in 31.8% (35/110) of belimumab-exposed women and 43.8% (7/16) of placebo-exposed women in clinical trials; 4.2% (2/48) of women in the BPR prospective cohort and 50% (4/8) in the BPR retrospective cohort; and 31.4% (43/137) of belimumab-exposed women from postmarketing/spontaneous reports. All belimumab-exposed women in clinical trials and the BPR received concomitant medications and had confounding factors and/or missing data. Conclusions: Observations reported here add to limited data published on pregnancy outcomes following belimumab exposure. Low numbers of exposed pregnancies, presence of confounding factors/other biases, and incomplete information preclude informed recommendations regarding risk of birth defects and pregnancy loss with belimumab use.